A 35-year-old father with persistent Mullerian duct syndrome and seminoma of the right undescended testis: a rare case report - Marah Mansour; Abdullah Fattal; Yassamine Ouerdane; Tamim Alsuliman; Omar Kanjawi (Surgical Case Reports, 2021)
Abstract Background A persistent Müllerian duct syndrome is a rare disorder of sexual differentiation characterized by the presence of the female reproductive system in a normal male. Case presentation Herein, we report a case of a 35-year-old father with persistent Müllerian duct syndrome and seminoma in the right undescended testis. The exploratory laparotomy was performed and revealed a mass in the right undescended testis and Müllerian duct structures. Conclusions For patients with cryptorchidism and inguinal hernia, the persistent Müllerian duct syndrome should be considered, and radiological evaluation of the genitourinary system is recommended for early diagnosis of persistent Müllerian duct syndrome. The persistent Müllerian duct syndrome is usually detected during a surgical operation, and it is considered a risk factor for developing testicular malignancies.